2015
DOI: 10.4067/s0034-98872015000400003
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento diagnóstico de la broncoscopia con biopsia transbronquial en el estudio de lesiones sugerentes de cáncer pulmonar

Abstract: (Rev Med Chile 2015; 143: 433-438)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Matsuda et al in his study concluded that the diagnostic yield of bronchial brushing ishigher than biopsy and that a combination of two techniques gives the highest percentage of positive diagnoses [17]. This is contraindication to the present study where biopsy yields higher positive results compared to bronchial brushing.…”
Section: Discussionmentioning
confidence: 62%
“…Matsuda et al in his study concluded that the diagnostic yield of bronchial brushing ishigher than biopsy and that a combination of two techniques gives the highest percentage of positive diagnoses [17]. This is contraindication to the present study where biopsy yields higher positive results compared to bronchial brushing.…”
Section: Discussionmentioning
confidence: 62%